Visualizing defects and pore connectivity within metal–organic frameworks by X-ray transmission tomography. Issue 24 (24th May 2021) - Mayorga-González, Rafael; Rivera-Torrente, Miguel; Nikolopoulos, Nikolaos; Bossers, Koen W.; Valadian, Roozbeh; Yus, Joaquín; Seoane, Beatriz; Weckhuysen, Bert M.; Meirer, Florian
Abstract : TXM-tomography unraveled large macropore defects within a MIL-47(V) MOF crystal. These pores do not seem to be well connected and they show a preferential orientation. Abstract : Metal–Organic Frameworks (MOFs) have the potential to change the landscape of molecular separations in chemical processes owing to their ability of selectively binding molecules. Their molecular sorting properties generally rely on the micro- and meso-pore structure, as well as on the presence of coordinatively unsaturated sites that interact with the different chemical species present in the feed. In this work, we show a first-of-its-kind tomographic imaging of the crystal morphology of a metal–organic framework by means of transmission X-ray microscopy (TXM), including a detailed data reconstruction and processing approach. Corroboration with Focused Ion Beam-Scanning Electron Microscopy (FIB-SEM) images shows the potential of this strategy for further (non-destructively) assessing the inner architecture of MOF crystals. By doing this, we have unraveled the presence of large voids in the internal structure of a MIL-47(V) crystal, which are typically thought of as rather homogeneous lattices. This challenges the established opinion that hydrothermal syntheses yield relatively defect-free material and sheds further light on the internal morphology of crystals.